Produção científica dos programas de pós-graduação stricto sensu em economia no Brasil e a formação de redes de pesquisadores: uma análise a partir dos professores permanentes no período de 2004 a 2011 - Furtado, Vanessa Viégas Alves (Universidade do Vale do Rio dos Sinos, 2013)
It was proposed in this study to analyze the scientific production of permanent teachers of stricto sensu graduate programs in Economics in Brazil, as well as to observe the formation of existing production networks among these teachers in the period from 2004 to 2011. For both, were collected at permanent teachers Lattes of 47 postgraduate programs that composed the sample, information on production of full papers published in journal seach one for the period under examination. After scheduled, this information formed the basis, not only to analyze the scientific production of permanent teachers, through indicators such as total score, average score for teaching staff, standard deviation of the mean score, percentage of productive teachers and international insertion level, from Qualis Stratum along with the score established by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) to the Economy in the year 2012but also look at how the formation of scientific production networks among these permanent teachers and interaction among its actors, through some of the main indicators of centrality, such as degree of Centrality index of centralization, degree of Proximity and degree of Intermediation. It is noteworthy that for the analysis of social networks and authorship of publications was used in this work the software Ucinet 6,445 for Windows version 6 (BORGATTI; EVERETT; FREEMAN, 2002), in concomitance with the NetDraw 2,123 version (BORGATTI, 2002) program responsible for illustrating these networks through graphs. The results showed that, despite the progressive decline in the number of actors for each analyzed period, that is, 2004-2006, 2007-2009 and 2010-2011, the formatting of the production networks of permanent teachers of stricto sensu graduate programs in economics in Brazil has not changed significantly, underscoring the incidence of various groups working in isolation, predominantly in trios or pairs, and crowded in the same graduate program, and some networks formed around a single actor who, by its strategic position, showed good amount of interconnections with other actors.
Keywords: Produção científica; Programas de pós-graduação; Redes de produção científica; Professores permanentes; Scientific production; Graduate programs; Scientific production networks; Permanent teachers; ACCNPQ::Ciências Sociais Aplicadas::Economia